2003
DOI: 10.1577/t01-135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrofishing Gear Type on Spatial and Temporal Variability in Fish Community Sampling

Abstract: Abstract.-Fish community data collected from 24 major river basins between 1993 and 1998 as part of the U.S. Geological Survey's National Water-Quality Assessment Program were analyzed to assess multiple-reach (three consecutive reaches) and multiple-year (three consecutive years) variability in samples collected at a site. Variability was assessed using the coefficient of variation (CV; SD/mean) of species richness, the Jaccard index (JI), and the percent similarity index (PSI). Data were categorized by three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…A sample collected from a representative reach (Fitzpatrick et al 1998, Barbour et al 1999) is assumed to be representative of community attributes along a larger stream segment (Rabeni et al 1999, Gregg and Stednick 2000, Meador and McIntyre 2003, even though others have shown that this assumption may be incorrect (Lenz and Rheaume 2000, Brigham and Sadorf 2001, Gebler 2004. Nevertheless, most segment-scale assessments are made from a single sample collected from a representative reach, and most investigators rarely report estimates of uncertainty.…”
Section: Discordance In Site Conditionmentioning
confidence: 99%
“…A sample collected from a representative reach (Fitzpatrick et al 1998, Barbour et al 1999) is assumed to be representative of community attributes along a larger stream segment (Rabeni et al 1999, Gregg and Stednick 2000, Meador and McIntyre 2003, even though others have shown that this assumption may be incorrect (Lenz and Rheaume 2000, Brigham and Sadorf 2001, Gebler 2004. Nevertheless, most segment-scale assessments are made from a single sample collected from a representative reach, and most investigators rarely report estimates of uncertainty.…”
Section: Discordance In Site Conditionmentioning
confidence: 99%
“…Per representative unit of effort, species richness in night electric fishing samples was higher than the other gears, supporting results from several studies that night electric fishing captures a high percentage of species present (Meador et al . ), reflects similar richness across multiple years of sampling (Meador & Pollock ) and captures more species than gillnets (Erős et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Most are a result of limitations with the available data. First, electrofishing is size-selective (Zalewski and Cowx 1990;Meador and McIntyre 2003). Small species (e.g., inland silverside Menidia beryllina, red shiner Cyprinella lutrensis, and western mosquito fish Gambusia affinis), known to occur in Lubbock lakes, were not captured during sampling and consequently were not included in the assessment.…”
Section: Discussionmentioning
confidence: 99%